Pengaruh Disiplin Belajar dan Motivasi Belajar terhadap Hasil Belajar Siswa dalam Pembelajaran Matematika di Sekolah Dasar - Ika Imroatul Jamilah; Risnawati Risnawati; M. Fikri Hamdani; Muhammad Amin (Journal on Education, 2024)
Specifically, three topics are the primary goals of this research: 1) How learning discipline impacts student learning outcomes in mathematic subjects; 2) How learning motivation impacts student learning outcomes in mathematic subjects; and 3) How learning discipline and learning motivation collaborate to influence student learning outcomes in subjects related to mathematic. This study used an ex post facto quantitative approach at SD Aulia Cendekia Islam School Pekanbaru, class V. The findings of the study indicate that: 1) T-count < t-table (-0.032 < 1.690) or sig. t > 0.05 (0.975<0.05) indicate a very weak influence between the learning discipline variables on student learning outcomes in mathematic lessons at SD Aulia Cendekia Islam School Pekanbaru. 2) The learning motivation variable at SD Aulia Cendekia Islamic School Pekanbaru has very little effect on students' learning outcomes in mathematic learning, with a t-count value of -0.421 and a significance value of 0.676. This is because t-count < t-table (-0.421 < 1.690) or sig. t < 0.05 (0.676>0.05). 3) A significant value of t-count 0.05, suggest that learning discipline and learning motivation have no effect on student learning outcomes in academic sessions. By obtaining a 0.006 R square value